The ‘righteousness of the children of God’ according to the First Epistle of John - Merwe, Dirk G. van der (Verbum et Ecclesia, 2023)
The author of the First Epistle of John predominantly addresses the ‘theological concept of righteousness’ in two pericopes: pericope 1 (1:5–2:2) concerns the ‘Righteousness of God’, and pericope 2 (2:28–3:12) explores the ‘Righteousness of God’s children’ from various perspectives. The adjective, δίκαιος, occurs twice (1:9 and 2:1) and the noun, ἀδικίας, appears once (1:9) in the first pericope. In the second pericope, the adjective, δίκαιος, occurs three times, the adjective δίκαια once and the noun, δικαιοσύνη, also three times. This research starts with a discourse analysis to determine semantic networks to be used for the structuring of the reasoning and rhetoric in this research. Network A: The environment and foundation of righteousness: The glorious and measureless love of God in the familia Dei . Network B: The revelation of the righteousness of God in Jesus. Network C: A rhetorical strategy to alert God’s children to live righteously: Contrasting statements. Network D: A rhetorical strategy to encourage God’s children to live righteously: Parousia. Network E: Those who do what is right are righteous – they cannot sin anymore. Intradisciplinary and/or interdisciplinary implications: The theological concept of righteousness is explored from various perspectives, integrating semantic networks from biblical theologies, systematic discourses and Christian spiritualities to unfold the significance of the environment and foundation of righteousness, the love of God in the familia Dei , and the encouragement to live righteously.
free